Evaluation of Increase in Retinal Thickness as Diagnostic Marker in Central Artery Occlusion - Wiest, Maximilian Robert Justus; Schuknecht, Angelika; Hamann, Timothy; Fasler, Katrin; Said, Sadiq; Bajka, Anahita; Muth, Daniel Rudolf; Barthelmes, Daniel; Blaser, Frank; Zweifel, Sandrine (Klinische Monatsblätter für Augenheilkunde, 2024)
Purpose To evaluate the increase in retinal thickness as a marker in predicting the onset of central retinal artery occlusions.Methods Retrospective clinical study conducted at one Swiss hospital. Electronic records were filtered for patients with artery occlusions. Optical coherence tomography data, including time between the imaging and ischemic event, were reviewed. Increase in relative retinal thickness was measured, defined as an increase in retinal thickness compared to the unaffected partner eye. This was correlated with the time from symptom onset. A cutoff value of relative increase of < 24.5% was applied, as suggested in previous studies. The results were compared to the time gathered from the electronic records, and sensitivity, specificity, positive predictive value as well as negative predictive value were calculated for predicting an ischemia time of < 4.5 h.Results Forty-two eyes from 41 patients with central artery occlusions were identified. Fourteen were female. Mean age was 66.4 ± 15.8 years. Initial corrected visual acuity was 2.41 ± 0.68 logMAR, and 2.13 ± 0.87 logMAR at the last follow-up (p > 0.05). Of eyes with a visual acuity of counting fingers (n = 38) or worse, 89.5% showed no improvement during follow-up, while eyes with logMAR 1 or better (n = 4) improved. Thirteen eyes (13 patients) presented within 4.5 h of the ischemic event. Four patients received i. v. thrombolysis, with visual recovery in one. In 12 eyes with an ischemia time of < 4.5 h, relative increase was below 24.5%. In the remaining 29 eyes with > 4.5 h, relative increase was below 24.5% in 4 eyes and above 24.5% in 25 eyes. This yielded a sensitivity of 92.3%, a specificity of 86.2%, with a positive predictive value of 75.0% and a negative predictive value of 96.2%.Conclusion Central retinal artery occlusion is associated with severe vision loss. There is no current established therapy. Parameters that objectify the presence of a therapeutic window for thrombolysis are gaining in importance as patient history is often imprecise. Relative retinal thickness increase proved a noninvasive imaging parameter demonstrating adequate performance in detecting patients within the therapeutic window of thrombolysis. Further investigation of this parameter in central retinal occlusion is warranted.
Keywords: retina; central retinal artery occlusion; OCT